Determination of phenolic composition and antioxidant activity in fruits, rhizomes and leaves of the white strawberry (Fragaria chiloensis spp. chiloensis form chiloensis) using HPLC-DAD-ESI-MS and free radical quenching techniques - Simirgiotis, Mario Juan (2010)
A comparative analysis of methanol extracts from fruits, rhizomes and leaves of the Chilean white strawberry (Fragaria chiloensis spp. chiloensis var chiloensis) was performed by means of reversed phase high-performance liquid chromatography coupled to diode array detection and electrospray ionization mass spectrometry (HPLC-DAD and HPLC-ESI-MS). The total phenolic, total flavonoid and total anthocyanin content of the extracts was measured and compared. For the first time, some 18 phenolic compounds were tentatively identified in rhizomes and 18 in leaves of the Chilean strawberry. The products were mainly procyanidins, ellagitannins, ellagic acid and flavonol derivatives. The different extracts of the native strawberry presented antioxidant activity, which was close to that exhibited by the white fruits. The rhizomes and leaves proved to be a good source of phenolic antioxidants. The obtained information can be used to characterize the local cultivars by metabolite profiling and provide a reference HPLC fingerprint for future comparison of chemical changes associated to the plant response towards environmental factors and pathogens.